THE USE OF COLLABORATIVE TECHNIQUE IN TEACHING SHORT STORY AT THIRD GRADE STUDENTS - Nur Antoni (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2022)
Teacher should utilize collaborative strategy when teaching short story writing since short story writing requires more stages to practice. The following are the objectives of this study: (1) to look into the process of teaching a short narrative using a collaborative approach; (2) to look into the process of teaching a short tale using a collaborative approach; (3) to look into the effects of employing collaborative learning to teach short stories; and (4) to look at the benefits of the teacher's method of teaching a short tale to third-grade pupils through collaborative tehcnique. This study used qualitative research with third-grade bidikmisi scholarship students at STAI Brebes as participants. Data was collected by observation, interview, and documentation. The data for this study came from a teacher and pupils in the third grade at STAI Brebes' bidikmisi scholarship program. The findings of this study revealed that employing collaborative writing in the classroom to teach short stories resulted in (1) students being able to develop their short story writing skills; (2) students were able to write a short story in Indonesian; (3) students were able to translate a short story into English; (4) students learned new vocabulary; and (5) students were able to assess grammar in the classroom. The benefits of teaching short stories through collaborative technique were as follows: (1) students were able to engage in social contact; and (2) students were able to explore ideas in short story writing.